English Medium Instruction: Support for students and professors in Gender art and Social Sciences. - Griffith-Bourn, Mary Margaret; Lechuga-Jiménez, Clotilde (My University, 2017)
This paper presents specific reference tools which continues the line started on the article published last year in 2nd International Conference on Higher Education Advances (HEAD ‘16) (Barrios, López-Gutiérrez & Lechuga, 2016), where we found that neither institutional language integrated support nor a specific language plan was being provided by the bilingual programme. This runs counter to experts’ opinion calling for the need of such a plan: “The English-taught degree programme requires a language plan of its own, which will be complementary to the larger university policy and plan… it is a necessity for ensuring a smooth and collaborative transition into English medium” (Marsh et al., 2013, p. 15). While studies show the importance of language support in bilingual instruction, they rarely address specific content professors' needs, tending to remain distant from real teaching contexts. The educational Innovation Project (PIE 15-100) provides professional development for subjects like Gender Art included in Social Sciences Education taught through the medium of English in the Primary Education degree at the University of Málaga. The title “Support for students and professors” means moving into the reality of the classrooms to address specific needs of this unique academic scenario. Firstly, the paper acknowledges a trend towards English Medium Instruction (EMI) in Higher Education while at the same time distinguishes EMI from adjunct CLIL (Brinton, Snow & Wesche, 2011) suggesting that more explicit language integration is needed. With this in mind, we present a professional development project for instructors which we will call the CLIL eye (Griffith, 2015). Secondly, we examine how language support has a dual focus that includes both students and instructors. Outlining these actions, the innovation project focuses on collaborative work, language support, and collective training in aspects related to a systematic monitoring of the experience. Finally, we will use a case study in which a glossary is integrated into a lecture and an external observer will provide assessment for the instructor on ways to improve discourse. The results indicate how, with this task design, language is supported as not only the language of learning, and as language through learning (Coyle, et al., 2010), but more specifically as the language for teaching. The paper concludes with a reflection on interdisciplinary innovation projects that provide professors with the tools they need to ensure the quality of bilingual programmes.
Keywords: Enseñanza bilingüe; Ciencias sociales - Estudio y enseñanza; English Medium Instruction; Higher Education; Social Sciences Education; Gender art